Drivers of Covid-19 Vaccinations: Vaccine Administration and Delivery Efficiency in the United States - Rajeev K. Goel; Michael A. Nelson (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper adds some formal research to the success of ongoing efforts to combat the COVID-19 pandemic by examining the drivers of the administration and delivery efficiency of coronavirus vaccines. For this purpose, we use data from the 50 US states and place the formal analysis in the context of socio-economic drivers of vaccinations. Results show that state economic prosperity and rural population aid vaccine administration and delivery efficiency. Delivery efficiency improves in states with more nursing homes per capita, in states with more COVID-19 deaths, and with more health workers. The subset of health workers, including physicians and nurses, did not significantly impact administration or efficiency. On the other hand, vaccination efficiency was lower in states with a centralized public health agency. States with a larger share of the elderly population and those with Democrats as governors were no different from others with regard to vaccinations. Robustness checks are performed using vaccination from a more recent period. Finally, a state's legacy of corrupt activity, across two different time dimensions, is broadly consistent with the greasing effects of corruption. While the study uses data from a single nation that is among the first to start vaccinating its population, the findings have relevance for other nations, especially in the Global South, that are starting vaccinations or lagging behind in delivering vaccines.
Keywords: H50; H75; I10; I18; K42; 330; Covid-19; coronavirus; vaccine; efficiency; rural; deaths; health workers; corruption; networking; United States